Theoretical Investigation on the Reaction Pathways of the Oxygen Reduction Reaction on Graphene Codoped with Manganese and Phosphorus as a Potential Nonprecious Metal Catalyst. Issue 21 (28th October 2016) - Bai, Xiaowan; Zhao, Erjun; Li, Kai; Wang, Ying; Jiao, Menggai; He, Feng; Sun, Xiaoxu; Yang, Jucai; Wu, Zhijian
Abstract: Nonprecious‐metal‐doped graphene catalysts have been proposed recently as promising candidates to substitute Pt catalysts for the oxygen reduction reaction (ORR) in fuel cells. We codoped Mn and P in divacancy graphene (MnP x, x =1–4) and we studied the stability and the catalytic activity for the ORR. The calculated formation energy indicates that MnP2 ‐doped divacancy graphene is energetically the most stable. The MnP2 moiety and its adjacent six C atoms are catalytically active sites for the ORR. The kinetically most favorable pathway is the hydrogenation of OOH to form O+H2 O, which is a four‐electron process. The rate‐determining step is the second H2 O formation, which has an energy barrier of 0.91 eV. The free energy diagrams show that for OOH hydrogenation into O+H2 O all of the elementary steps are downhill at potentials of 0.0–0.67 V except for the second H2 O formation. Abstract : A theoretical calculation : An inexpensive and sustainable nonprecious metal MnP‐codoped graphene electrocatalyst is designed by employing spin‐polarized DFT. The kinetically most favorable pathway is the hydrogenation of OOH to form O+H2 O in the oxygen reduction reaction, which is a desired four‐electron process.